LRC-KJHAM ROLE IN PROMOTING GENDER POLICY JUST IN SEMARANG 2015 - Kusuma Achmad Harianto; Budi Setiyono; Fitriyah . (Journal of Politic and Government Studies, 2016)
Role LRC-KJHAM as an NGO to participate fairly in an effort menguaatkanpolicies that gender background of this study, an attempt LRC-KJHAM is caused bythe high level of violence against women in the city, as we know the productsregulation will confirm the seriousness of the government and place them onprovisions which are more powerful and binding in law enforcement.As for gender equality or gender equity by USAID is an attempt to achieveequal conditions between men and women. This research was conducted usingqualitative descriptive method, research location is the office of LRC-KJHAM, officeBAPERMAS Women and KB Semarang and Village Krobokan, while the method ofrecruitment of informants is through purposive sampling method, the subject of thisstudy is, Chief Operating LRC-KJHAM, Division Head of Women Empowerment ofWomen and Family Planning BAPERMAS the city, and a community representativesample is then taken caretaker Working Group I Sub Krobokan. The type and sourceof the data itself in the form of primary data results of interviews and secondary dataobtained from a number of books, documents and other sources are used and obtainedduring the study. Data collection techniques such as interviews, observationdefinitions and documentation studies. The data analysis technique itself throughData Collection, data Data Reduction, Display Data and Verification and AssertionsConclusions.In findings in the field of policy advocacy efforts LRC-KJHAM realizedthrough efforts to encourage ratification of the draft law on Maternal and Child SafetySemarang. It is obtained from the informant, chairman of Working Group I Krobokanvillage who attended the meeting between the LRC-KJHAM, Member of ParliamentCommission D Semarang and community representatives (women's groups) at theHotel Ibis in Semarang discuss harmonization efforts bylaw Mother and Child Safety.So that we can conclude there is a role-KJHAM LRC to encourage gender-equitablepolicies through the meeting, it was also revealed that there is good coordinationbetween the LRC-KJHAM and stage the existing holder.